Çocuğun Dinî Gelişiminde Rol Model Olarak Anne ve Baba - Koç, Bozkurt (Dinî araştırmalar, 2008)
Family is an institution through whose basic principles of society, customs and traditions, value judgments, beliefs and ideals are transferred to child. Family which reflects the culturel values of society to child is also a place where child gains its first experiences. While learning how to be social individual, child needs a model with which it will identify himself. Members of family, parents in particular, are the most important models who have a direct or indirect influence on the child. They are the role models who play a considerable part in the religious development of children as well as in their psychological, emotional and social developments. In this article, the influence of parents as a role models on the religious development of child has been dealt with